The search for ecologies of knowledge in the encounter with African epistemicide in South African education - Aslam Fataar, Aslam Fataar; Subreenduth, Sharon (South African Journal of Higher Education, 2016)
This article discusses the manufactured absence of African epistemologies, what we refer to as ‘epistemicide, in formal education in Africa. The exemplifying case for our argument is the western hegemonic positioning of university and school-based knowledge in South African education during the last twenty years. This is taken up in the first half of the article where we illustrate how this (westernised) knowledge form is instantiated in the education body politik. The article concludes with a consideration of an ‘ecologies of knowledge’ approach which we argue opens a radicalising space for the inclusion of African-centred epistemologies. The pluralisation of knowledge traditions, via an ‘ecologies of knowledge’ approach, is the fulcrum of such an epistemological orientation.